Citation for the Down Surgical Prize 1998 - P.J. LEOPARD (Blackwell Synergy, 2000)
It is a rare if not unique event for the Down Surgical Prize to be awarded to the incumbent President of this Association and it gives me great pleasure to act in loco presidentia for a few minutes.